C‐Reactive Protein, Bone Strength, and Nine‐Year Fracture Risk: Data From the Study of Women's Health Across the Nation (SWAN). (18th June 2013) - Ishii, Shinya; Cauley, Jane A; Greendale, Gail A; Crandall, Carolyn J; Danielson, Michelle E; Ouchi, Yasuyoshi; Karlamangla, Arun S
ABSTRACT Higher levels of C‐reactive protein (CRP), an inflammatory marker, are associated with increased fracture risk, although previous studies on CRP and bone mineral density (BMD) have yielded conflicting results. We aimed to test the hypotheses that composite indices of femoral neck strength relative to load, which are inversely associated with fracture risk, would also be inversely associated with CRP, and would explain part of the association between CRP and fracture risk. We analyzed data from a multisite, multiethnic prospective cohort of 1872 community‐dwelling women, premenopausal or early perimenopausal at baseline. Femoral neck composite strength indices in three failure modes were calculated using dual‐energy X‐ray absorptiometry (DXA)‐derived femoral neck width (FNW), femoral neck axis length (FNAL), femoral neck BMD and body size at baseline, as BMD*FNW/weight for compression strength, BMD*(FNW)2/(FNAL*weight) for bending strength, and BMD*FNW*FNAL/(height*weight) for impact strength. Incident nondigital, noncraniofacial fractures were ascertained annually over a median follow‐up of 9 years. In analyses adjusted for age, race/ethnicity, diabetes, menopause transition stage, body mass index, smoking, alcohol use, physical activity, medications, prior fracture, and study site, CRP was associated inversely with each composite strength index (0.035–0.041 SD decrement per doubling of CRP, all p < 0.001), but not associated with femoral neck or lumbar spine BMD. During the follow‐up, 194 women (10.4%) had fractures. In Cox proportional hazards analyses, fracture hazard increased linearly with loge(CRP), only for CRP levels ≥ 3 mg/L. Addition of femoral neck or lumbar spine BMD to the model did not attenuate the CRP‐fracture association. However, addition of any of the composite strength indices attenuated the CRP‐fracture association and made it statistically nonsignificant. We conclude that fracture risk increases with increasing CRP, only above the threshold of 3 mg/L. Unlike BMD, composite strength indices are inversely related to CRP levels, and partially explain the increased fracture risk associated with inflammation.